How to store araticum seeds and maintain their physiological quality: Storage periods and packaging of araticum. - Silva, Edvan Costa da; Villa, Fabíola; Silva, Daniel Fernandes da Silva; Possenti, Jean Carlo Possenti; Masiero, Michel Anderson Masiero; Cruz, Maria Soraia Furtado Vera (Comunicata Scientiae, 2024)
The purpose of seed storage is its preservation; in this sense, the storage period and types of packaging materials utilized in this process interfere with the conservation of seed vigor. The objective here was to evaluate the physiological potential of araticum seeds in different types of packaging materials and storage periods. The work was developed at the State University of Western Paraná Seed Technology Laboratory (Unioeste) - Campus Marechal C. Rondon - from February to August 2020. The seeds were packed in different packaging materials for three months (February, March, and April / 2020), kept in a cold chamber (16º C and 40% RH). The experimental design used was completely randomized, in a 5 x 7 factorial scheme [five packages (glass, plastic bag, burlap bag, kraft paper, and pet bottle) x seven storage periods (0, 15, 30, 45, 60, 75 and 90 days)]. It is important to note that araticum seeds have dormancy, so they were submerged in 500 mg L-1 of gibberellic acid (GA3) for 24 hours before the setting up of the germination test. Evaluating the physiological aspect of the germination and vigor. The kraft paper packaging is the most suitable for storing araticum seeds. The physiological potential of seeds of this species decreases when its storage period is increased.